2016
DOI: 10.1038/srep26499
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Analysis of Tissue Interstitial Fluid for Identification of Novel Serum Candidate Diagnostic Marker for Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the fifth most common malignant cancer in the world. The sensitivity of alpha-fetoprotein (AFP) is still inadequate for HCC diagnosis. Tissue interstitial fluid (TIF), as the liquid microenvironment of cancer cells, was used for biomarker discovery in this study. Paired tumor and nontumor TIF samples from 6 HBV-HCC patients were analyzed by a proteomic technique named iTRAQ (isobaric tag for relative and absolute quantitation). Totally, 241 up-regulated proteins (ratio ≥ 1.3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Eight‐plex isobaric tags for relative and absolute quantitation (iTRAQ) analysis was performed in the State Key Laboratory of Proteomics (Beijing Proteome Research Center, National Center for Protein Sciences Beijing). Sample preparation, mass spectrometry, peptide and protein identification were performed as previously described (Wang et al ., ; Sun et al ., ; Zhang et al ., ). All reported data were recorded using Excel for evaluation of candidate proteins based on proteomic fold‐change and false discovery rate (FDR).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight‐plex isobaric tags for relative and absolute quantitation (iTRAQ) analysis was performed in the State Key Laboratory of Proteomics (Beijing Proteome Research Center, National Center for Protein Sciences Beijing). Sample preparation, mass spectrometry, peptide and protein identification were performed as previously described (Wang et al ., ; Sun et al ., ; Zhang et al ., ). All reported data were recorded using Excel for evaluation of candidate proteins based on proteomic fold‐change and false discovery rate (FDR).…”
Section: Methodsmentioning
confidence: 99%
“…Usually, haemophagocytic macrophages in the bone marrow, peripheral blood or tissue samples are regarded as the hallmark of HLH, but these may not be present or be easily found at the early stage, leading to diagnostic difficulty (Zhang et al, 2011;Larroche, 2012;Maruoka et al, 2014). Particularly in the early stages of L-HLH, the clinical symptoms and laboratory results often do not formally fulfil the diagnostic HLH-2004 criteria, further leading to under-or delayed diagnosis of HLH in patients (Tamamyan et al, 2016;Lin et al, 2017).…”
Section: Haemophagocytic Lymphohistiocytosismentioning
confidence: 99%
See 2 more Smart Citations
“…demonstrated that versican core protein (VCAN) is a potential biomarker for early HCC diagnosis by label-free discovery analysis: selected (multiple) reaction monitoring (SRM/MRM)20. It was also reported that protein S100A9, which was dramatically up-regulated in sera from HCC patients, is a candidate HCC diagnostic biomarker21. Lu used the mass spectroscopic approach to characterize the metabolic features of the liver in HCC patients and verified that serum acetylcarnitine was a meaningful biomarker reflecting HCC diagnosis and progression22.…”
Section: Discussionmentioning
confidence: 99%